Grown ups - Keyes, Marian (Doubleday Canada, 2020)
They're a glamorous family, the Caseys. Johnny Casey, his two brothers Ed and Liam, their beautiful, talented wives and all their kids spend a lot of time together--birthday parties, anniversary celebrations, weekends away. And they're a happy family. Johnny's wife, Jessie--who has the most money--insists on it. Under the surface, though, conditions are murkier. While some people clash, other people like each other far too much . . . Still, everything manages to stay under control--that is, until Ed's wife, Cara, gets a concussion and can't keep her thoughts or opinions to herself. One careless remark at Johnny's birthday party, with the entire family present, and Cara starts spilling all their secrets. As everything unravels, each of the adults finds themselves wondering if it's--finally--the time to grow up.